THE EFFECT OF THE TRADITIONAL MA'GURECCENG GAME IN IMPROVING THE NUMERACY SKILLS OF STUDENTS AT SD NEGERI 24 PANDANG-PANDANG - Asmaul Husna; Aisyah Nursyam; Aspikal Aspikal (Jurnal Penalaran dan Riset Matematika, 2025)
Elementary school students need to have numeracy skills from an early age because these skills are an important foundation for solving various everyday problems that require logical thinking. The main objective of this study was to identify the relationship between the use of the traditional game Ma'gurecceng and the level of numeracy skills of students studying at SD Negeri 24 Pandang-Pandang. The use of the traditional game Ma'gurecceng is considered relevant as a learning medium that not only attracts students' interest but is also effective in strengthening their numeracy skills. The research was conducted using a quantitative method with a pre-experimental design in the form of a one-group pre-test-post-test. All 12 fifth-grade students at SD Negeri 24 Pandang-Pandang were selected as participants using a saturated sample method. Data were collected through written tests involving pre-tests and post-tests as well as student response questionnaires. Furthermore, data processing used the Wilcoxon test to compare pre-test and post-test scores. Statistical tests proved that after participating in learning activities with the Ma'gurecceng game, students' numeracy skills increased significantly. The average post-test score (81.58) was higher than the pre-test score (49.92), while the Wilcoxon test using SPSS gave a result (Sig.) of 0.002 (p < 0.05). The questionnaire data showed that 57.5% of respondents "strongly agreed," 42.5% "agreed," with no "disagree" or "strongly disagree" responses. The research findings confirm that the application of the traditional Ma'gurecceng game has a beneficial contribution to improving students' numeracy skills.